WEAK CONVERGENCE OF FIXED POINT ITERATIONS IN METRIC SPACES - Raj, S. I.; Moorthy, C. G. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2013)
The concept of convergence in normed spaces is extended to metric spaces; and weak convergence of fixed point iterations of contractions on metric spaces is obtained in this article.